Exercise-induced changes in amino acid levels in skeletal muscle and plasma - Keisuke Ishikura (Journal of Physical Fitness and Sports Medicine, 2013)
During exercise, amino acid oxidation and protein breakdown are enhanced while protein synthesis is suppressed, even though protein does not constitute a quantitatively important energy source. In response to exercise-induced stimulation, various changes in free amino acids occur in skeletal muscle to meet physiological demands. Plasma amino acids are also under the influence of various types of stress, including exercise stress. For example, acute exercise increases alanine and glutamine levels, but decreases glutamate levels in skeletal muscle. At the same time, it increases tryptophan and taurine levels, but decreases glutamine levels in plasma. Prolonged exercise decreases glutamine and glutamate levels, while increasing tyrosine and phenylalanine levels in skeletal muscle. Furthermore, when prolonged exercise-induced changes in amino acid levels are compared between trained and untrained individuals, glutamate and taurine levels in skeletal muscle and phenylalanine, leucine, isoleucine, and tyrosine levels in plasma are higher in trained individuals. This review provides an overview of changes in amino acid levels in skeletal muscle and plasma, with a focus on changes induced by exercise.